Isolation and identification of bacteria micro flora of white shrimp, litopenaeus vannamei, with antagonistic properties against Vibrio species - Far, Hadi Zokaei; Saad, Che Roos; Mohd Daud, Hassan; Kamarudin, Mohd Salleh; Fard, Ehsan Ramezani (Academic Journals, 2013)
The emergence of antibiotic-resistant bacterial pathogen has led aquaculture attentions to the use of probiotics as an alternative to antibiotics. This study was conducted to isolate bacterial micro flora from digestive tract of healthy juvenile white shrimp, Litopenaeus vannamei based on antagonistic activity against shrimp pathogen, Vibrio parahaemolyticus. In this study, potential probiotic strains were isolated using replica plating method to screen the bacteria with antagonism properties. Six isolates were identified as Pseudomonas sp. using conventional biochemical tests and Biolog GN microplates. In addition three Vibrio species including V. parahaemolyticus, Vibrio alginolyticus and Vibrio cholerae were isolated from moribund shrimp and used as pathogen in this study. The pathogenicity of three Vibrio species was tested on shrimp L. vannamei by injecting 0.1 mL of 107 CFU mL-1 of each pathogen into the third abdominal segment. Among three Vibrio species only V. parahaemolyticus found to be highly virulent to shrimp with 43% cumulated mortality after 10 days. Subsequently, all Pseudomonas sp. isolates were tested for antibacterial activity against three Vibrio species using cross streak assay. Strong antibacterial activity was recorded for Pseudomonas sp. isolates number 5, 7, 15 and 30 against three pathogens. In addition a reasonable antibacterial activity was observed for isolates number 9 and 12. On the basis of great antibacterial activity of Pseudomonas sp. isolates these species may be considered for future challenge experiments in shrimp as a very promising alternative to the use of antibiotics.